A Relationship Between the Curvature Tensor and the Difference Tensor for Affine Hypersurfaces - Joaquín, Daniel A. (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2020)
In the present work, it is obtained a class of hypersurfaces, of decomposable type, for which the curvature tensor associated to the affine normal connection, and the Levi-Civita covariant derivative of the difference tensor, are scalar multiples each other.